Urban boosterism in closed contexts : spectacular urbanization and second-tier mega-events in three Caspian capitals - Valiyev, Anar; Koch, Natalie (Routledge, 2015)
This paper presents a case study of urban boosterism in Azerbaijan, Kazakhstan, and Turkmenistan – three resource-rich states around the Caspian Sea. Boosterist projects are typically justified through the injunction of, “build it and they will come.” This cliché is a staple of how urban planners and elites seek to justify development schemes that lack an obvious demand. And while the logic underpinning urban boosterism hinges on a high degree of openness and freedom of movement – both for capital and people – it is a tactic increasingly being used in closed and otherwise illiberal states. Understanding the effects of this development is an important task as a growing number of urban planners in nondemocratic but resource-rich countries seek to develop spectacular new urban landscapes and position their cities as “world class” hubs for international mega-events – even if these are smaller, second-tier events. Exploring event-oriented urban development in Astana, Ashgabat, and Baku, we show how boosterist narratives are being re-deployed in closed contexts to promote the image of a benevolent and “magical state,” as well as solidifying authoritarian political configurations and a selective engagement with market capitalism.
Eurasian Geography and Economics
Keywords: Urban renewal -- Azerbaijan.; Urban renewal -- Kazakhstan.; Urban renewal -- Turkmenistan